Long-Term Effects of Metformin and Lifestyle Modification on Nonalcoholic Fatty Liver Disease Obese Adolescents - Lian Tock; Ana R. Dâmaso; Aline de Piano; June Carnier; Priscila L. Sanches; Henrique Manoel Lederman; Regina M. Y. Ernandes; Marco Túlio de Mello; Sérgio Tufik (Journal of Obesity)
Objective. To assess the long-term effects of metformin in combination with lifestyle intervention and its association between insulin levels and the degree of steatosis at ultrasonography (US) in obese adolescents. Methods. Thirty-five postpubertal obese boys were randomized into two groups: one receiving metformin in combination with a multidisciplinary lifestyle intervention versus a placebo group, which also received the same intervention. The visceral, subcutaneous fat and degree of steatosis were measured by ultrasonography. Fasting blood samples were collected to analyze glucose, insulin, insulin resistance, and aminotransferases. Repeated ANOVA measures were used to compare changes over time and between groups, and Spearman's correlations were used to identify an association between insulin and the degree of steatosis at US. Results. There was a positive correlation between the degree of steatosis at US with insulin concentrations and HOMA-IR. Long-term therapy plus metformin significantly reduced body weight, body mass index, insulin, HOMA-IR, and visceral fat. Conclusions. Metformin was more effective than the placebo in improving clinical parameters associated with obesity and steatosis.